Technological Challenges and Solutions in Hydrothermal Vent Energy Development for Indonesia's Energy Resilience - Ardyanto, Fakhriyan; Thamrin, Suyono; Widayatno, Rudy Laksmono (International Journal of Technology and Education Research, 2025)
Indonesia's exceptional geothermal position along the Pacific Ring of Fire presents the nation with an opportunity to develop hydrothermal vent energy as a significant renewable resource, with a potential estimated at 29,000 megawatts. However, despite this promise for energy resilience, formidable technological barriers have prevented the practical implementation of deep-sea thermal systems. This study investigates the primary technological challenges through systematic literature analysis and descriptive research, examining six critical domains: material durability and corrosion resistance, subsea engineering design and equipment reliability, thermal energy extraction and efficiency, infrastructure deployment and maintenance, ecosystem protection, and regulatory frameworks. By synthesizing findings from academic research, government reports, and industry expertise, the research reveals both substantial obstacles and emerging solutions. At the same time, challenges are significant, encompassing material degradation, system reliability, thermodynamic efficiency, and deep-sea deployment. Practical pathways forward exist through the use of advanced materials, innovative engineering, rigorous testing, and adaptive environmental management. The study proposes a phased implementation strategy that progresses from research and pilot demonstrations through technology refinement to commercial deployment. This work offers essential guidance for policymakers, engineers, and energy security specialists seeking to harness Indonesia's hydrothermal potential while maintaining environmental sustainability, operational reliability, and advancing national energy resilience.